Leading Causes of Mortality and Prescription Drug Coverage in Canada and New Zealand - Rawson, Nigel S. B. (Frontiers in Public Health, 2020)
Introduction: Canada may soon see the introduction of a national pharmaceutical insurance system. New Zealand has a government-funded healthcare system used by all residents that operates within a tight cost-containment budget. The objective of this analysis was to compare the main mortality causes in Canada and New Zealand and examine listings in current Canadian provincial public drug plans and the New Zealand national drug formulary. Materials and Methods: Age-standardized mortality rates from 2000 to 2015 and data on hospital discharges and average length of stay in hospital for Canada and New Zealand were obtained from the Organization for Economic Cooperation and Development's website. Information on insured medications was obtained from Canadian provincial drug plan lists and the New Zealand Pharmaceutical Schedule current in mid-2019. Results: Hospital discharge rates for cardiovascular disorders, malignancies and respiratory disorders and mortality rates for acute myocardial infarction, ischemic heart disease and cerebrovascular disease were higher, on average over the observation period, in New Zealand than in Canada, but mortality rates for malignancies and respiratory disorders were similar. Reimbursement listing rates for cancer drugs and some cardiovascular medications were lower in New Zealand than in Canada. Discussion: Higher hospital discharge and mortality rates suggest poorer patient health in New Zealand compared with Canada. This may be due to lower reimbursement listing rates for some medications in New Zealand. New Zealand's drug coverage system has contained costs, but it restricts or denies access to new innovative medicines with the potential to improve patients' lives. Although a New Zealand-style national pharmacare scheme in Canada would offer the opportunity to restrain drug expenditure, it would likely fail to satisfy patients and healthcare providers and could diminish health outcomes, resulting in higher costs in other healthcare sectors.